Annual report of Reproductive Endocrinology Committee, Japan Society of Obstetrics and Gynecology, 2013. Issue 2 (February 2014) - Minegishi, Takashi; Sugino, Norihiro; Ishihara, Osamu; Kitawaki, Jo; Harada, Tasuku; Murakami, Takashi
Abstract The Japan Society of Obstetrics and Gynecology Reproductive Endocrinology Committee summarizes the activities of each subcommittee below from April 2011 to March 2013. Survey for clinical outcomes of infertility treatment for women with adenomyosis and complications of pregnant women with adenomyosis. Survey for multiple pregnancies after controlled ovarian stimulation in non‐assisted‐reproductive‐technology infertility treatment cycles: population‐based study in Japan. Study on the effect of endometriosis management on ovarian reserve.